Use of Mammalian Target of Rapamycin Inhibitors for Pancreas Transplant Immunosuppression Is Associated With Improved Allograft Survival and Improved Early Patient Survival. Issue 5 (May 2019) - Siskind, Eric J.; Liu, Chang; Collins, Devon T.; Emery, Erica; Steen, Erin; Tran, Emily; Stodghill, Joshua; Piper, James; Jonsson, Johann; Ortiz, Jorge
Abstract : Objectives: Mammalian targets of rapamycin inhibitors (mTORi) are considered second-line immunosuppression agents because of associated increases in rejection and impaired wound healing. Recent reports indicate mTORi have been linked to improved survival, decreased inflammatory response in pancreatitis, and antiproliferative and antiangiogenic activity. Mammalian targets of rapamycin inhibitors have not been extensively analyzed in pancreas transplant recipients. Methods: Adults with pancreas and kidney-pancreas transplants from 1987 to 2016 in the United Network for Organ Sharing database were analyzed (N = 25, 837). Subjects were stratified into 2 groups: use of mTORi (n = 4174) and use of non–mTORi-based immunosuppression (n = 21, 663). The log-rank test compared survival rates. Univariate and multivariate Cox regression analyses assessed patient and graft survival. Results: Mammalian targets of rapamycin inhibitors were associated with a 7% risk reduction in allograft failure (hazard ratio, 0.931; P = 0.006). Allograft survival rates were significantly different between mTORi versus non-mTORi ( P < 0.0001).The mTORi group showed a significantly higher patient survival rate 1, 3, 5, and 10 years posttransplant compared. Patient survival at 15 years was not significantly different. Conclusions: The use of mTORi for immunosuppression in pancreas transplant is associated with improved allograft survival and early patient survival posttransplant (up to 10 years).